1990
DOI: 10.1002/jmor.1052050110
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and ultrastructural study of the alimentary tract of the freshwater snail Lymnaea stagnalis

Abstract: The alimentary tract of the freshwater snail Lymnaea stagnalis, except the salivary glands and the digestive gland, was studied with histochemical and ultrastructural methods. The main focus was on the epithelia. Previous studies have indicated that the digestive gland, where intracellular digestion occurs, plays the major role in the digestion process. The main cell types of the tract are ciliated cells and cells with microvilli. The presence of ciliated cells reflects transport of food particles and faeces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…The digestive gland has significant capacity to assimilate (primarily via cellular uptake) dissolved and particulate nutrients and compounds (Carriker, 1946;Boer & Kits, 1990). Our detection of toxin in snails beyond 8 h corresponds favorably with Veldhuijzen (1974), who demonstrated that fine and soluble digestible matter assimilated by digestive gland cells might remain detectable for at least 100 h postingestion.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The digestive gland has significant capacity to assimilate (primarily via cellular uptake) dissolved and particulate nutrients and compounds (Carriker, 1946;Boer & Kits, 1990). Our detection of toxin in snails beyond 8 h corresponds favorably with Veldhuijzen (1974), who demonstrated that fine and soluble digestible matter assimilated by digestive gland cells might remain detectable for at least 100 h postingestion.…”
supporting
confidence: 70%
“…Findings on gross morphological, ultrastructural and histochemical aspects (Carriker, 1946;Boer & Kits, 1990) and particle sorting and retention time (Veldhuijzen, 1974) within the alimentary tract of Lymnaea are summarized in Table 2. Coarse, indigestible plant matter passes from the gizzard into the pylorus, where ciliary sorting of food particles by size and digestibility occurs.…”
Section: -H Gut Clearance Studymentioning
confidence: 99%
“…stagnalis seems well equipped to serve this function. Especially the mid-and post-intestine contain areas showing all morphological characteristics of water-and salttransporting epithelia (Boer and Kits 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was adopted since it was impossible (within a reasonable period of time) to dissect out the complete digestive system without damaging it. The first part, ''digestive gland'', contained the digestive gland (carrying the largest lumen of the alimentary system; supposed to contain almost all radioactivity), the post-oesophagus, the crop and the gizzard, the pylorus and the vestibulum, the pro-intestine, mid-intestine and the largest part of the post-intestine (Boer and Kits 1990). Besides the ovotestis and its duct, no other organs were present in this fraction.…”
Section: Surgerymentioning
confidence: 99%
“…Basic reagents commonly used included Alcian blue, azure A, and other thiazines such as thionin and toluidine blue, aldehyde fuchsin and iron diamines [Spicer and Schulte, 1992;Yamada, 1993;Schumacher and Adam, 1994]. These conventional methods alone [Bremer, 1987;Gilks et al, 1988;Boer and Kits, 1990;Chieffi-Baccari et al, 1990;Gonzalez de Canales et al, 1992;Saint-Girons and Zylberberg, 1992] or in combination with lectins [Danguy andGenten, 1989, 1990;Genten and Danguy, 1990a-c;Castells et al, 1991;Getchell and Mellert, 1991;Sharma and Schumacher, 1992;Uhr et al, 1993] have successfully been employed as reported in the given selection of recent papers of glycan histochemistry.…”
Section: Conventional Histochemistry Of Complex Glycansmentioning
confidence: 99%